Case Series of Rare Cases of Osteomyelitis - Suresh, Saurabh; Mane, Shailaja; Awase, Shivshankar; Patil, Manoj; Maheshwari, Abhinav (Journal of Neonatal Surgery, 2025)
Background: Inflammation of the bone and bone marrow, primarily from infection in the medullary cavity, is the hallmark of osteomyelitis. It spreads to the periosteum and quickly consumes the haversian system. Compared to today's time and era, osteomyelitis of the jaws was in fact a common discovery prior to the widespread use of antibiotics. Odontogenic infections can be caused by a number of organisms that cause osteomyelitis of the jaws, including Peptostreptococcus, Fusobacterium, Prevotella, Staphylococcus aureus, and Staphylococcus epidermidis. Case summary: A 3 years old female child presented with complaints of bilateral mandibular swelling and Dental caries since 2 months. On examination the patient had bilateral swelling which was firm in consistency, non-mobile adhered to underlying structure, non-tender, 4*5cm in size. The child was treated with 6 weeks of iv antibiotics for resolution of the symptoms. The 2nd case is a 10 years old male child came to OPD with complain of recurrent localized swelling in the mandibular region and Pain and difficulty in opening his mouth for the past 4 months. Intermittent fever persisting for 1 month. The 3rd case is of a 2 years old female child presented with low grade fever, subside intermittently with oral medications, associated with pus discharge from bilateral ear. CT scan of all 3 patients revealed that osteomyelitis on underlying mandible and maxilla. Conclusion: Since maxillary osteomyelitis is one of the rarest types of osteomyelitis that occurs nowadays, diagnosing it might be challenging. There is a dearth of information on the epidemiology of maxillary osteomyelitis in India, which emphasizes the necessity of thorough investigation.